Profil KLT Partisi Etil Asetat Ekstrak Metanol Daun Sirih Hitam (Piper betle L. Var Nigra) - Natanael Ramos Parapat; Fajar Prasetya; Sabaniah Indjar Gama; M Arifuddin (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Black betel leaves are widely used for various treatments, one of which is oral diseases such as gingivitis and dental caries by Indonesians. The purpose of this study was to determine the class of compounds and to find the best eluent for the separation of compounds from methanol extract. This research begins with extraction using the maceration method withmethanolsolvent. The extract obtained was tested using analytical TLC to find the best eluent. After obtaining the best eluent, the partition extraction of black betel leaf methanol extract was carried out using ethyl acetate. The ethyl acetate soluble and ethyl acetate insoluble extractswere separated then the three extracts were continued with the identification of the compounds by analytical TLC using the two best eluent comparisons that had been done previously and then observed under UV light 254 nm and 366 nm after that sprayed using Dragendorff reagent and FeCl3. The best eluent analysis result of ethyl acetate partition of black betel leaf methanol extract was n-hexane:ethyl acetate (6:4, 3:1) and TLC analysis showed that the compounds contained were alkaloids and phenolic.